Vitamin D in pediatric age: Current evidence, recommendations, and misunderstandings - Corsello, Antonio; Spolidoro, Giulia C. I.; Milani, Gregorio P.; Agostoni, Carlo (Frontiers in Medicine, 2023)
In recent years vitamin D has been in the spotlight of many researchers for its possible role in various disorders, including autoimmune and infectious diseases. Even if vitamin D deficiency remains a major public health problem, its symptomatic manifestations are less and less common in clinical practice, and pediatric age represents a “gray area” where vitamin D supplementation is often administered in the absence of an effective evaluation of its status. Moreover, a poor knowledge about different definitions of “deficiency,” “insufficiency,” and similar terms is spread among clinicians, while guidelines are not univocal, especially after the first year of life. The aim of this brief opinion paper is to sum up recent evidence about vitamin D status and its supplementation in pediatrics, in order to better clarify a common definition of its deficiency. The aim of this opinion article is to raise awareness on this topic among clinicians and encourage a discussion on the real need for routine 25-hydroxycholecalciferol serum evaluation and its supplementation.